Excitation of eigen azimthal waves by annular charged particle beam - Girka, V.; Lapshin, V.; Puzyrkov, S. (Вопросы атомной науки и техники, 2005)
Investigations of an interaction between charged-particle beams and hybrid waveguide structures are important for radio engineering and plasma electronics. It is the distinctive feature of the interaction between charged particle beams and such structures of finite dimensions that motivated the choice of the subject for our study. Here we investigate the excitation of an extraordinarily polarized electromagnetic azimuthal waves (AW), that are eigen modes of a cylindrical metal waveguide partially filled with a cold magnetized plasma. These modes propagate in azimuthal direction strictly transverse to a constant external axial magnetic field. A two-dimensional self-consistent set of differential equations for interaction between AW and cold low-density charged-particle beam moving above the plasma surface is constructed in the single-mode approximation and is solved numerically. Constructed nonlinear theory can be applied for modeling an operation of short-scale plasma filled devices capable of generating continuously tunable radiation over a broad frequency band (eigenfrequency of the plasma structure can be continuously tuned by varying the plasma density). Influence of nonuniformity of charged particle beam distributions in co-ordinate and phase spaces on evolution of beam-driven instability of the AW are examined. Дослідження взаємодії між потоками заряджених частинок та гібридними хвилеводними структурами є важливим для радіофізики та плазмової електроніки. В даній статті досліджено збудження незвичайно поляризованих електромагнітних азимутальних хвиль, які є власними модами циліндричного металевого хвилеводу, який частково заповнено холодною магнітоактивною плазмою. Двовимірна самоузгоджена система диференціальних рівнянь була виведена для опису нелінійної взаємодії між азимутальними хвилями та потоком заряджених частинок малої густини, який рухається над поверхнею плазми, та досліджена числовими методами в одномодовому наближенні. В роботі досліджено вплив неоднорідності розподілу потоку заряджених частинок в координатному та фазовому просторах на еволюцію пучкової нестійкості азимутальних хвиль. Исследование взаимодействия потока заряженных частиц с гибридными волноводными структурами представляется важным для радиофизики и плазменной электроники. В данной статье исследовано возбуждение необыкновенно поляризованных электромагнитных азимутальных волн, которые являются собственными модами цилиндрического металлического волновода, частично заполненного холодной магнитоактивной плазмой. Двумерная самосогласованная система дифференциальных уравнений была выведена для описания нелинейного взаимодействия между азимутальными волнами и потоком заряженных частиц малой плотности, двигающимся над поверхностью плазмы, и исследована числовыми методами в одномодовом приближении. В работе исследовано влияние неоднородности распределения потока заряженных частиц в координатном и фазовом пространствах на эволюцию пучковой неустойчивости азимутальных волн.